Analysis of science literacy skills of students of the Biology Education Study Program, Labuhanbatu University - Rabiatul Adawiyah; Ika Chastanti (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
Science literacy skills are a person's ability to apply scientific knowledge to real-world situations. This study aims to analyze students' science literacy skills. This research uses a qualitative descriptive method that aims to describe carefully and systematically the facts and nature of a particular population. The sample in this study was 56 students of Biology Education, Faculty of Teacher Training and Education, University of Labuhanbatu. The sampling technique uses purposive sampling. Data collection techniques in the form of essay tests and questionnaires. Data analysis techniques using the Miles and Huberman Model. The results of the study showed that the science literacy ability of students of the Biology Education Study Program was still classified as